Mixture traces probabilistic analysis in the comparison of several hypotheses - Andrade, M. A. P.; Ferreira, M. A. M. (Acta Scientiae et Intellectus, 2018)
The objective of this work is to discuss various approaches in the analysis of DNA mixture profiles, starting with a mixture trace with only two contributors and extending the analysis to a larger number of contributors. Both the algebraic treatment and the use of OOBN are considered concluding with the inevitability of using the latter in more complex situations.